Influence of 5-Hydroxytryptamine, 5-Hydroxytryptophan. Dopamine, Norepinephrine, and Reserpine on Thrombotic Deposits in the Rabbit - Baumgartner, Hans-Rudolf; Studer, Alfred; Reber, Kurt (Thrombosis and Haemostasis, 1964)
5-hydroxytryptamine (5-HT, serotonin) and its precursor 5-hydroxytryptophan (5-HTP) significantly inhibit in rabbit blood vessels formation of thrombotic deposits, a term used by us to specify platelet aggregates on the intima ringed by leucocytes, resulting from intimai injury. Simultaneous inhibition of monoamine oxidase by Nialamide clearly enhances this action of 5-HT and 5-HTP. The marked activity of the combination of 5-HT + Nialamide is not limited to the initial phase of thrombogenesis, but is discernible at a weaker level 30 minutes and even as long as 24 hours after intimai injury. The monoamines dopamine and norepinephrine exert, as reserpine, no influence on the formation of thrombotic deposits.These results underline the importance of 5-HT in the initial events of thrombogenesis. They support the hypothesis that inhibition of the formation of thrombotic deposits is in some manner related to an interaction between 5-HT, blood platelets and possibly vessel wall.